Analisis Pelayanan Transportasi Massal Dalam Memenuhi Perjalanan Masyarakat di Wilayah Mamminasata (Studi Kasus : Teman Bus Trans Mamminasata di Kota Makassar ) - Truly Andira Salsabilah S; S Kamran Aksa; Rimba Arief (Fakultas Teknik Universitas Bosowa, 2022)
The aim of this research is to understand how the process massal transportation services in fulfilled society’s journey in the city of Makassar. This research was conducted by a quantitative and qualitative methods to answer the services of Teman Bus (Trans Mamminasata) in order to fulfilled the travel needs of the people in the city of Makassar. The process of data collection through observation, documentation, interviews and questionnaires and also use the method of proportional samples. The data is analyzed by using borda analysis in the form of grouping, where instruments are based on the Target of the Minister of Transportation Regulation Number: KM.49 of 2005 concerning the National Transportation System (Sistranas). From 14 instruments, it is shown that the Teman Bus (Trans Mamminasata) service that affects people's travel is an safety instrument, comfort and affordable rate so that it can be concluded that the society’s judgements about Teman Bus (Trans Mamminasata) has a high level of safety during operation and the realization of tranquility, passengers could feel safety and comfortable while in Teman Bus (Trans Mamminasata), more than that this transportation also could offer low rate price that suitable with the purchasing power of society in Makassar.